Treatment of brain metastases from non-small cell lung cancer: preclinical, clinical, and translational research - Sampat, Parth J.; Cortese, Alyssa; Goodman, Alexandra; Ghelani, Ghanshyam H.; Mix, Michael D.; Graziano, Stephen; Basnet, Alina (Frontiers in Oncology, 2024)
Lung cancer is the second most common type of cancer and is the leading cause of cancer-related deaths in the United States. Approximately 10-40% of patients with solid tumors develop brain metastases, with non-small cell lung cancer accounting for approximately 50% of all cases of patients with brain metastases. Many management options are available which can include surgery, radiation, and systemic therapy. A variety of factors go into the selection of management of brain metastases. In this review, we will focus on the treatment strategies and optimizing the management of brain metastases in patients with non-small cell lung cancer.